2021
DOI: 10.26803/ijlter.20.10.13
|View full text |Cite
|
Sign up to set email alerts
|

Beyond Play: Conceptualising the Capability of a Good Digital Game to Stimulate Interest in STEM

Abstract: Digital games are one of the potential pedagogical approaches within STEM teaching and learning. The main idea behind using digital games in STEM contexts is to enhance the children’s conceptual understanding and to increase their interest in STEM. The interest in STEM is still an unsolved global issue. Most studies looking into digital games show there to be positive implications when it comes to STEM learning. This gap and the uncorrelated scenario from both the theoretical and practical perspectives need to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 56 publications
1
13
0
Order By: Relevance
“…However, the three-design method practice can be simplified towards more universal attributes. These review findings correlated with the idea in most recent studies [25,86], where the elements within the discovered approaches can be extracted and grouped into theory, learning strategy, pedagogy, learning content, game elements, and game principle design. These six main classifications potentially serve as universal attributes for digital game design for educational purposes.…”
Section: Looking Forward and Future Perspectivesupporting
confidence: 67%
See 2 more Smart Citations
“…However, the three-design method practice can be simplified towards more universal attributes. These review findings correlated with the idea in most recent studies [25,86], where the elements within the discovered approaches can be extracted and grouped into theory, learning strategy, pedagogy, learning content, game elements, and game principle design. These six main classifications potentially serve as universal attributes for digital game design for educational purposes.…”
Section: Looking Forward and Future Perspectivesupporting
confidence: 67%
“…Designing and developing games in education is complicated due to the incorporation of educational content, game elements, and entertainment [6,18,24,25]. The purpose is to engage players to the game play and enhance learning.…”
Section: Designing Games For Dgblmentioning
confidence: 99%
See 1 more Smart Citation
“…Determining the content of games is recognized as one of the important aspects of SGs design for children [ 34 , 40 ]. The studies indicated that learning content is identified as a universal attribute in SEGs and plays a crucial contribution in constructing good instructional games [ [48] , [49] , [50] ]. These results show the important role of learning content in children's games.…”
Section: Discussionmentioning
confidence: 99%
“…An analysis of the state of the art indicates that educators are reluctant to adopt this technology for many reasons such as poor understanding of pedagogical issues and difficulties in integrating the technologies with their existing content (Mutambara, Bayaga and Others, 2020;Chaipidech et al, 2021;Gandolfi, Ferdig and Kratcoski, 2021). Furthermore, deploying these technologies in practice is also a challenge and researchers have found that educators lack the required resources and support (Ishak, Din and Hasran, 2021). A lack of student engagement and poor inclusiveness of students has also emerged as challenges (Lee and Choi, 2011;Kayan Fadlelmula, Sellami and Le, 2022).…”
Section: Introductionmentioning
confidence: 99%